Challenges and strategies for the identification and correction of patient–ventilator asynchronies in daily practice: a scoping review - Andrés Mauricio Enríquez Popayán; Katerina Vaporidi; Henry Mauricio Parada-Gereda; Lluís Blanch (Acute and Critical Care, 2026)
Patient–ventilator asynchronies (PVA) are associated with adverse clinical outcomes, including prolonged ventilatory support and increased mortality both in the intensive care unit (ICU) and at the hospital level. Despite their clinical relevance, the detection and management of PVA remain challenging in daily practice because of multiple factors, such as the lack of continuous monitoring and the low recognition by healthcare professionals. The aim of this review is to map and synthesize the available evidence on the main challenges in the identification and management of PVA and to describe the strategies proposed to overcome them. We conducted a scoping review following Joanna Briggs Institute guidance and reported in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR). PubMed/Medline, Scopus, ScienceDirect, LILACS, and the Cochrane Library were searched from inception to April 2025. Two reviewers independently screened records and selected eligible studies. Data were charted using a standardized extraction form, and findings were synthesized descriptively. The identified challenges were categorized into three main groups, and the proposed strategies were classified according to the type of challenge addressed. The scoping review included 33 studies published between 2000 and 2025. Of these, 17 provided explanatory evidence, whereas 16 described strategies for addressing challenges in daily clinical practice. Overall, this scoping review identified 15 distinct challenges. This review highlights the multifaceted challenges affecting the recognition and management of PVA in adult ICU patients. By mapping challenges across clinical, structural, and cultural domains and summarizing strategies to address them, this review provides professionals with a practical framework to improve patient–ventilator interaction.